THE LIFE HISTORY AND FEEDING HABITS OF A TRIPOD FISH (TRIACANTHUS :aREVIROSTRIS TEMM.& SCHLEG.) OF THE INDIAN SEA - KUTHALINGAM,M. Sc., Ph. D., F. A.Z, Dr. M.D. K. (TREUBIA, 1959)
abstract not available